2017
DOI: 10.1111/1365-2435.13000
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive physiological markers demonstrate link between habitat quality, adult sex ratio and poor population growth rate in a vulnerable species, the Cape mountain zebra

Abstract: Abstract1. Effective conservation and species management require an understanding of the causes of poor population growth. Conservation physiology uses biomarkers to identify factors that contribute to low individual fitness and population declines.Building on this, macrophysiology can use the same markers to assess how individual physiology varies with different ecological or demographic factors over large temporal and spatial scales.2. Here, we use a macrophysiological approach to identify the ecological and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 82 publications
(128 reference statements)
0
31
0
2
Order By: Relevance
“…For example, poor body condition in snowshoe hare Lepus americanus (Boonstra & Singleton, 1993) and marine iguanas Amblyrhynchus cristatus (Romero & Wikelski, 2001) was associated with higher stress levels and with poorer survival perspectives. Similarly, Lea et al (2018) found that cape mountain zebras Equus zebra zebra living in relatively lower quality habitat had highest faecal glucocorticoid concentrations, which were negatively correlated with long-term population growth and female fecundity. One possible explanation of the association between glucocorticoids and relative population abundance might lie with energy budget as survival probability decreases in individuals whose stress levels cause long-term energy needs that exceed energy intake (McEwen & Wingfield, 2003).…”
Section: Discussionmentioning
confidence: 87%
“…For example, poor body condition in snowshoe hare Lepus americanus (Boonstra & Singleton, 1993) and marine iguanas Amblyrhynchus cristatus (Romero & Wikelski, 2001) was associated with higher stress levels and with poorer survival perspectives. Similarly, Lea et al (2018) found that cape mountain zebras Equus zebra zebra living in relatively lower quality habitat had highest faecal glucocorticoid concentrations, which were negatively correlated with long-term population growth and female fecundity. One possible explanation of the association between glucocorticoids and relative population abundance might lie with energy budget as survival probability decreases in individuals whose stress levels cause long-term energy needs that exceed energy intake (McEwen & Wingfield, 2003).…”
Section: Discussionmentioning
confidence: 87%
“…Habitat quality (from resource composition and availability) predicted density or population size in the Great Crested Newt Triturus cristatus (Unglaub et al, 2018) and the Grizzly bear Ursus arctos (Lamb et al, 2018). In the Cap mountain zebra Equus zebra zebra, lower resource availability influenced individual physiology, in turn affecting population growth rate (Lea et al, 2018). In the mud crab Panopeus herbstii, habitat quality (reef height, in the field) and the diet (in the lab) impacted on the reproductive performance of females (Griffen and Norelli, 2015).…”
Section: Resource Availability or Resource Configuration: What Is Thementioning
confidence: 99%
“…Lea et al. 's study () is important because it convincingly demonstrates how a non‐invasive macrophysiological approach can be used at a metapopulation scale to evaluate on‐going conservation strategies. Although the exact causes relating higher androgen levels in males to low female fecundity and poor population performance in the Cape mountain zebra remain to be determined (e.g.…”
mentioning
confidence: 99%
“…In a new study, Lea et al (2018) use a macrophysiology approach to identify potential causes of poor population growth in a vulnerable species, the Cape mountain zebra (Equus zebra zebra) (Ripple et al, 2015). Macrophysiology is the investigation of physiological trait variations over large geographical and temporal scales and the ecological implications of these variations (Chown, Gaston, & Robinson, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation